Slower Peak Pupillary Response to Emotional Faces in Parents of Autistic Individuals - Hogan, Abigail L.; Winston, Molly; Barstein, Jamie; Losh, Molly (Frontiers in Psychology, 2022)
Background: Atypical autonomic arousal has been consistently documented in autism spectrum disorder (ASD) and is thought to contribute to the social-communication phenotype of ASD. Some evidence suggests that clinically unaffected first-degree relatives of autistic individuals may also show subtle differences in indices of autonomic arousal, potentially implicating heritable pathophysiological mechanisms in ASD. This study examined pupillary responses in parents of autistic individuals to investigate evidence that atypical autonomic arousal might constitute a subclinical physiological marker of ASD heritability within families of autistic individuals. Methods: Pupillary responses to emotional faces were measured in 47 ASD parents and 22 age-matched parent controls. Macro-level pupillary responses (e.g., mean, peak, latency to peak) and dynamic pupillary responses over the course of the stimulus presentation were compared between groups, and in relationship to subclinical ASD-related features in ASD parents. A small ASD group (n=20) and controls (n=17) were also included for exploratory analyses of parent-child correlations in pupillary response. Results: Parents of autistic individuals differed in the time course of pupillary response, exhibiting a later primary peak response than controls. In ASD parents, slower peak response was associated with poorer pragmatic language and larger peak response was associated with poorer social cognition. Exploratory analyses revealed correlations between peak pupillary responses in ASD parents and mean and peak pupillary responses in their autistic children. Conclusions: Differences in pupillary responses in clinically unaffected parents, together with significant correlations with ASD-related features and significant parent-child associations, suggest that pupillary responses to emotional faces may constitute an objective physiological marker of ASD genetic liability, with potential to inform the mechanistic underpinnings of ASD symptomatology.